Strategi Brand Activation pada Event Bandung Thrift Weekend - Muhammad Rafif Ariztiawan; Yulianti (Bandung Conference Series: Communication Management, 2023)
Abstract. Humans in general have a tendency to always follow the changes and developments of the times. One of them is changes and developments in clothing trends. Thrifting is an activity to buy used goods and Bandung Thrift Weekend is the first thrifting event to accommodate thrifting activists and as a Brand Activation of Discover Ideas. This study uses a qualitative method with a case study approach. The conclusion of the results of this study are (1) Brand Activation through Social Media Activation is carried out on the Instagram, TikTok and Website platforms in order to be an approach to the audience and potential audiences. (2) Brand Activation through Marketing Event Activation is carried out through the creation of the Bandung Thrift Weekend thrift market event. Which makes the event a pioneer of thrift events in Indonesia. (3) The concept selection conducted at Bandung Thrift Weekend came from a reference to a similar event that had been conducted in Los Angeles, USA. With a touch of creative approach from the activation of other communities in the Bandung Thrift Weekend event, it is a differentiator from the thrift event that is the reference. Abstrak. Manusia pada umumnya memiliki kecenderungan untuk selalu mengikuti perubahan dan perkembangan zaman. Salah satunya yaitu perubahan dan perkembangan pada tren berpakaian. Thrifting merupakan sebuah kegiatan membeli barang-barang bekas layak pakai dan Bandung Thrift Weekend menjadi event thrifting pertama untuk mewadahi para penggiat thrifting dan sebagai Brand Activation dari Discover Ideas. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Kesimpulan hasil dari penelitian ini adalah (1) Brand Activation melalui Social Media Activation dilakukan pada platform Instagram, TikTok dan Website guna menjadi pendekatan kepada audiens dan calon audiens. (2) Brand Activation melalui Marketing Event Activation dilakukan melalui pembuatan event thrift market Bandung Thrift Weekend. Yang mana menjadikan event tersebut sebagai pelopor event thrift di Indonesia. (3) Pemilihan konsep yang dilakukan di Bandung Thrift Weekend berasal dari referensi event serupa yang sudah dilakukan di Los Angeles, USA. Dengan sentuhan creative approach dari aktivasi komunitas lainnya yang ada di event Bandung Thrift Weekend menjadi pembeda dari event thrift yang menjadi referensinya.